2021
DOI: 10.20525/ijrbs.v10i3.1155
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and teachers’ attitude towards online classes during Covid-19 pandemic

Abstract: In this paper, students, and teachers' attitudes towards shifting to an entirely online learning environment were assessed due to COVID-19.  The main objective of the study was to investigate the students’ and teachers' attitudes towards Online learning during the COVID-19 situation in Bangladeshi Government Colleges. Findings revealed that cost and time-effectiveness, safety, convenience, and improved participation were the most frequently cited positive aspects of the online learning experience, while distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…For example, Hekmat said, "it was very helpful for us in saving time; during face-to-face classrooms, we had to go to university four days a week from 1 PM to 5 PM, however, during the online classes, we had no time limitation." The above results are in line with Afroz et al (2021) findings. They found that the online classes were safe, convenient, and time-saving during the COVID-19 pandemic.…”
Section: Opportunitiessupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Hekmat said, "it was very helpful for us in saving time; during face-to-face classrooms, we had to go to university four days a week from 1 PM to 5 PM, however, during the online classes, we had no time limitation." The above results are in line with Afroz et al (2021) findings. They found that the online classes were safe, convenient, and time-saving during the COVID-19 pandemic.…”
Section: Opportunitiessupporting
confidence: 92%
“…Doucet, Netolicky, Timmers, and Tuscano (2020) found that the online platforms enhanced collaboration opportunities, creative solutions, and interest in learning from teachers, learners, and parents. It was also found that online classes were safe, convenient, and time-saving during the COVID-19 pandemic (Afroz et al, 2021). Similarly, findings from Almahasees et al (2021) revealed that online learning was inexpensive, convenient, and improves self-learning and flexibility.…”
Section: Online Learning Opportunitiesmentioning
confidence: 88%
“…In general, the responses of the teachers who participated in this study confirmed the gaps found by several studies in the implementation of online learning or distance education, specifically in terms of access to and the use of technology, both for teachers and their students, teacher skills, and experience, the availability of resources, and the adaptation of online platforms (Coman et al, 2020;Moralista & Oducado, 2020;Afroz et al, 2021). Although half of the respondents had experience in preparing distance education, such as PowerPoint Presentations, a greater number were not adequately prepared for distance learning; and they lacked experience in preparing distance-learning modules, which were required during the pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…A similar conclusion was formulated by Händel et al (2020). Afroz et al, (2021) have analyzed attitudes towards online e-learning during COVID-19 in Bangladesh. They found out that the cost and time effectiveness, safety, convenience and improved participation constitute positive elements of the online experience, whereas distraction, reduced focus, heavy workload, technological problems, lack of ICT skills, and low attendance of learners are among the negative elements.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Thanks to the existence of distance learning platforms such as Zoom and MS Teams (Ismaili, 2021), this task has become possible to implement in an efficient and effective way. There are numerous research works concerning the students' experience during the pandemic that investigate various aspects of this topic, including factors influencing positive student attitude towards online learning (Afroz et al, 2021), student preferences ____________________________________________________________________ _____________________ Dariusz DYMEK, Mariusz GRABOWSKI and Grażyna PALIWODA-PĘKOSZ, Journal of e-Learning and Higher Education, DOI: 10.5171/2022.881022 (Rippe et al, 2021;Steward and Lowenthal, 2021;. However, to the best of our knowledge, an investigation of changes in behavioral patterns of online activities, including online learning, has not been conducted in a comprehensive way.…”
Section: Introductionmentioning
confidence: 99%